PERCERAIAN ORANG TUA DAN IMPLIKASINYA TERHADAP PENDIDIKAN ANAK DALAM ISLAM - Rima Hadayati (Raudhah - Proud To Be Professional, 2016)
Every child is born in a state of nature, then both his parents who make it Jewish, or Zoroastrian Nashrani (HR.Muslim). Implied meaning of the hadith is that the formation of the child's personality is influenced by upbringing and education of parents. Basically every child wants to live with his parents, didikik, nurtured and given affection filled by both parents. However, if the household of his parents could not be maintained in this case happens disharmony or other factors so that his parents divorced, the children are victims of divorce of their parents. Divorce for children is "a sign of the death of" the unity of the family, it was half of the "self" has lost a child, life will never be the same again after their parents divorced and they have to accept the grief and sense of loss is profound. such children should harbored a deep sense of longing for a father or mother who suddenly does not live with him anymore. The negative effect of divorce on the development and education of children are: children get less attention, affection, and educational demands of parents, the need for physical and psychological teen is not consummated, the children do not get physical exercise and mental indispensable for moral life, divorce of parents expected to affect the learning achievement of children, both in the field of religious studies as well as in other fields, improve the delinquency of children, influence the formation of the child's personality.